Memberdayakan Guru Melalui Google Sites dan Pendekatan Science, Technology, Engineering, Mathematics-Deep Learning - Rilia Iriani; Ayu Tri Khodizah; Yogo Dwi Prasetyo; Arif Sholahuddin; Leny; Misna Yulianti (Jurnal Pemberdayaan Masyarakat, 2026)
There is a rising interest in the Deep Learning approach, which has been recognized as an effective teaching model, especially when combined with STEM and digital learning for innovation. Discussions with Chemistry Teachers’ Working Group (MGMP) in the Banjar Regency highlighted some difficulties, namely the lack of teachers’ competency in the creation of digital learning materials; the application within the local wetland environment; and the implementation of STEM-Deep Learning. In an effort to overcome the challenges, this community service initiative aimed to upgrade teachers’ competency in a training activity on the creation of digital learning materials employing Google Sites combined with STEM-Deep Learning implementation. A three-day community service involving 26 active teachers recommended by the MGMP program included activities like training/learning, practice, and the presentation of digital learning designs in the form of websites. This program provided a clear indication that the teachers succeeded in adapting the learning website with contextual chemistry content. Moreover, the teachers’ competency in digital literacy, creativity, and the teachers’ concern were upgraded. Teachers responded positively despite some limitations regarding the time constraint and teachers’ digital literacy. This initiative has contributed directly to the improvement of the quality of education.